ANALISIS PENGARUH DEBT CAPITAL DAN EQUITY CAPITAL TERHADAP SISA HASIL USAHA (SHU) KOPERASI - Adih Supriadi (EkoPreneur, 2019)
This study is entitled Analysis of the Effect of Debt Capital and Equity Capital on the Remaining Operational Results of Cooperatives. The research is descriptive quantitative, the population used as the unit of research analysis is the Cooperative in the City of South Tangerang with the category thirty large cooperatives in the City of South Tangerang, with the criteria of having more than one business unit, and routinely carrying out RATs  the last three years in a row. The number of cooperatives that will be sampled in this study are thirty cooperatives. The research method used is causal analytical associative meaning a causal relationship where the variable x will affect the variable y. This method aims to determine the relationship between two or more variables, by explaining, predicting and controlling a symptom. The purpose of this study was to determine the effect of Debt Capital and Equity Capital on the Remnants of Cooperative Business Results in the City of South Tangerang. From the results of the study note that Debt Capital partially has a significant effect on the Remaining Operating Results, with a coefficient of determination of 72.29%, the remaining 27.71% is influenced by other factors. Equity Capital partially has a significant effect on the Remaining Results of Operations, with a coefficient of determination of 74.67%, the remaining 25.33% is influenced by other factors. Debt Capital and Equity Capital simultaneously have a significant effect on the Remaining Operating Results, with a coefficient of determination of 81.81%, the remaining 18.19% is influenced by other factors.Keywords: Cooperative, Debt Capital, Equity Capital, Remaining Operating Results